The global diversity of Haemonchus contortus is shaped by human intervention and climate - G. Sallé (Nature Portfolio, 2019)
Based on single worm whole genome sequencing, the authors here characterise the global evolution of the gastrointestinal parasite Haemonchus contortus and identify genes that play a role in drug resistance as well as climate-driven adaptations involving an epigenetic regulator.